'Psychiatry is a risk business': the construction of mental health service users as objects of risk: a multiple case study inquiry - Felton, Anne (2015)
The emergence of recovery as an important philosophy in contemporary mental health care, alongside increasing levels of coercion has drawn attention to the potential for conflicting influences in mental health practice. This thesis examines how such conflicts may be situated in the historical, legal and professional foundation of mental health services, presenting an argument to suggest this exposes mental health professionals to tensions in decision-making.